INFLUENCE OF BRAND AWARENESS, BRAND ASSOCIATION, PERCEIVED QUALITY, AND BRAND LOYALTY OF TIKTOK SHOP | TOKOPEDIA ON PURCHASE DECISION - Anjelita, Adelia; Salim, Muhartini (jfpublisher, 2025)
E-commerce in Indonesia is growing fast, with TikTok Shop and Tokopedia becoming increasingly popular platforms. Many factors such as brand awareness, brand association, perceived quality, and brand loyalty are crucial in impacting consumer purchasing decisions. This research aims to analyze the influence of Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty on consumer purchase decisions at TikTok Shop | Tokopedia, both partially and simultaneously. This research applies quantitative methods with non-probability sampling techniques, specifically purposive sampling, in sample selection. Data was collected through an online questionnaire using Google Forms, which was distributed to active users who had made purchase transactions at TikTok Shop | Tokopedia. The population of this research consisted of at least 100 respondents. Data analysis was carried out using the Multiple Linear Regression method. The results showed that Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty have a positive and significant influence on purchasing decisions, both partially and simultaneously. Therefore, companies should improve their branding strategies to strengthen these four aspects to encourage purchasing decisions and maintain customer loyalty.